Investigation of guanosine-quartet assemblies by vibrational and electronic circular dichroism spectroscopy, a novel approach for studying supramolecular entities - Setnicka, Vladimír; Urbanová, Marie; Volka, Karel; Nampally, Sreenivasachary; Lehn, Jean-Marie (Chemistry (Weinheim an der Bergstrasse, Germany), 2006)
The self-assembly of guanosine-5'-hydrazide G-1 in D(2)O, in the presence and absence of sodium cations, has been investigated by chiroptical techniques: electronic (ECD) and the newly introduced vibrational (VCD) circular dichroism spectroscopy. Using a combination of ECD and VCD with other methods such as IR, electron microscopy, and electrospray ionization mass spectrometry (ESI-MS) it was found that G-1 produces long-range chiral aggregates consisting of G-quartets, (G-1)(4), subsequently stacked into columns, [(G-1)(4)](n), induced by binding of metal cations between the (G-1)(4) species. This process, accompanied by gelation of the sample, is highly efficient in the presence of an excess of sodium cations, leading to aggregates with strong quartet-quartet interaction. Thermally induced conformational changes and conformational stability of guanosine-5'-hydrazide assemblies were studied by chiroptical techniques and the melting temperature of the hydrogels formed was obtained. The temperature-dependent experiments indicate that the long-range supramolecular aggregates are dissociated by increasing temperature into less ordered species, monomers, or other intermediates in equilibrium, as indicated by MS experiments.
Keywords: termodynamika; Microscopy, Electron; cirkulární dichroismus; guanosin; elektronová mikroskopie; hydrogely; Spectrophotometry, Infrared; Electronics; elektronika; Guanosine; Thermodynamics; Molecular Conformation; Hydrogels; Circular Dichroism; Binding Sites; molekulární konformace; biomedicínský výzkum; spektrofotometrie infračervená; hmotnostní spektrometrie s elektrosprejovou ionizací; vazebná místa; Spectrometry, Mass, Electrospray Ionization; Biomedical Research